Salinomycin inhibits growth of pancreatic cancer and cancer cell migration by disruption of actin stress fiber integrity - Schenk, Miriam; Aykut, Berk; Teske, Christian; Giese, Nathalia; Weitz, Jürgen; Welsch, Thilo (Cancer letters, 2015)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by aggressive growth, early metastasis and high resistance to chemotherapy. Salinomycin is a promising compound eliminating cancer stem cells and retarding cancer cell migration. The present study investigated the effectiveness of salinomycin against PDAC in vivo and elucidated the mechanism of PDAC growth inhibition. Salinomycin treatment was well tolerated by the mice and significantly reduced tumor growth after 19 days compared to the control group (each n = 16). There was a trend that salinomycin also impeded metastatic spread to the liver and peritoneum. Whereas salinomycin moderately induced apoptosis and retarded proliferation at 5-10 µM, it strongly inhibited cancer cell migration that was accompanied by a marked loss of actin stress fibers after 6-9 h. Salinomycin silenced RhoA activity, and loss of stress fibers could be reversed by Rho activation. Moreover, salinomycin dislocated fascin from filopodia and stimulated Rac-associated circular dorsal ruffle formation. In conclusion, salinomycin is an effective and promising compound against PDAC. Besides its known stem cell-specific cytotoxic effects, salinomycin blocks cancer cell migration by disrupting stress fiber integrity and affecting the mutual Rho-GTPase balance.
Epub 2014 December 18
Gesehen am 18.06.2020